(untitled) (Annals of Medical Research, 2021)
Aim: To evaluate pediatric patients subjected to thoracic trauma in terms of prognosis, diagnosis and treatment. Although studies on trauma in adults are aplenty, those on the pediatric population are rarely available.Material and Methods: 261 patients who were exposed to thoracic trauma for any reason in the last 24 hours of hospital admission were included. The patients’ demographic data, etiology, treatments and results were retrospectively evaluated.Results: Our sample consisted of 85 girls and 176 boys with a mean age of 9.73±5.71 (range: 1-18 years). 228 of the patients (87%) had blunt trauma, 26 (10%) had penetrating trauma, and 7 (3%) had both penetrating and blunt trauma. Rate of penetrating trauma was about 4 times higher in boys. Traffic accidents were the most common reason for traumas. The most commonly fractured ribs were the 6th-9th ribs. 75 patients (28.7%) required tube thoracostomy, and 12 required open surgery. Rigid bronchoscopy was performed in 12 patients.Conclusion: None of the 33 patients with penetrating trauma died, contrary to the information in the literature. We found boys to be exposed to trauma more than girls (B/G: 2.07/1), albeit at different rates compared to the findings of other research. The development of rib fractures was found to be a predisposing factor for hemothorax. Hemothorax was observed in the 6th-9th ribs and in ≥4 rib fractures